Grammatical tense and focalization. Towards the problem of narrative distance in French literature - Kyloušek, Petr (Bohemica Olomucensia, 2015)
The article focuses on one of the aspects of narrator's perspective, or to be more specific, the focalization, for which we propose the term narrative distance. It is not the question of perspective but rather the question of phenomenological intention that is by means of focalization shown in the relation between the narrator and the narrated, or between the narrating instance that implies possible readers and the narrated world the parts of which the characters may be. This configuration is dynamic and variable when reading the text. To grasp it means to specify and better distinguish the setting of meaning in narrative strategies. Our ideas follow the articles by French theorists and are based on the analyses of French works of fiction. It is so, among other reasons, because the French verbal system shows better the language features that are discussed here than the Czech one. Therefore, the French as well as the French literary texts are mentioned in the first place. However, we believe that the outcomes of this article are general and may be applied to Czech literature too, no matter how different its language code and operations and means are.
Keywords: Focalization; narrative distance; narrative strategy; grammatical tense; French literature